Analysis of the coincidence rate between imaging and pathological findings of pulmonary metastasis in 45 cases with invasive bone and soft tissue sarcoma. Issue 2 (March 2015) - Huang, Zhen; Chen, Keneng; Kang, Xiaozheng; Zhang, Qing; Hao, Lin; Li, Yuan; Niu, Xiaohui
Abstract Background It is not uncommon for imaging examinations of invasive bone and soft tissue sarcoma patients during initial treatment or postoperative follow‐up to detect pulmonary nodules. This has important significance in determining the nature of nodules either for tumor staging and therapeutic regimen selection or for prognosis evaluation. Methods A review was carried out of invasive bone and soft tissue sarcoma patients diagnosed and treated in the department of orthopedic oncology of Beijing Jishuitan Hospital from June 2002 to June 2012. Data from patients who developed pulmonary metastases, diagnosed by imaging and treated surgically, were analyzed for consistency between imaging and postoperative pathological diagnoses. Results A total of 45 patients with pulmonary metastasis diagnosed by imaging and treated with resection of pulmonary lesions were included in the study. Thirty‐eight cases with pulmonary metastases (84.4%) and seven cases without pulmonary metastases (15.6%) were confirmed by postoperative pathological examination. The most common pathological type in the latter patients was tuberculosis, with a total of four cases (57.1%). Conclusion There is a certain degree of misdiagnosis when using imaging for diagnosis of pulmonary metastasis, and attention should be paid to the pathological diagnosis of pulmonary metastasis in order to avoid overtreatment. Tuberculosis is most common in invasive bone and soft tissue sarcoma patients with pulmonary benign lesions, and it should be distinguished.